TRANSFER TACIT KNOWLEDGE DALAM MENDUKUNG PENGEMBANGAN KARIER PROFESIONAL EDITOR DI LIPI PRESS - Suhendra, Muhammad; Laksmi, Laksmi (BACA: Jurnal Dokumentasi dan Informasi, 2024)
In general, the publishing industry is run by a staff of editors with non-specialist qualifications otherwise known as the "unintentional profession". Editors learn the skills to work 'on the job' (lesson learned) with more senior colleagues up to a certain time until deemed worthy and appropriate for promotion. Therefore, tacit knowledge plays an important role in supporting the editor's career in publishing. This study aims to answer the question of how the practice of transferring tacit knowledge is aimed at supporting the career development of editors at LIPI Press. Data collection was conducted in April-May 2021 using qualitative methods. Data was collected through a literature review, in-depth interviews with eight informants, and the active participation of researchers in observing document searches as a medium for lessons learned. The results show that most of the tacit knowledge transfer processes occur in editorial activities, which include socialization, externalization, combination, and internalization activities, both formally and informally. In this case, the greatest support felt by the editors was internalization in the form of knowledge sharing or flexibility in informal discussions, such as mentoring and coaching colleagues. In addition, this activity is also the most dominant or often carried out compared to other SECI stages, because the informal internalization process is felt to be more flexible and dynamic to exchange ideas, opinions, criticize, and understand a topic or problem being discussed. Finally, this study concludes that publishing activities based on knowledge of human resources require an adequate approach to understanding the social and strategic aspects of organizations so that they can support individual achievement and collaborative excellence, namely the transfer of knowledge, access to resources, and capabilities complete each other.